2016
DOI: 10.1073/pnas.1523004113
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-responsive in vitro RNA structurome of Yersinia pseudotuberculosis

Abstract: RNA structures are fundamentally important for RNA function. Dynamic, condition-dependent structural changes are able to modulate gene expression as shown for riboswitches and RNA thermometers. By parallel analysis of RNA structures, we mapped the RNA structurome of Yersinia pseudotuberculosis at three different temperatures. This human pathogen is exquisitely responsive to host body temperature (37°C), which induces a major metabolic transition. Our analysis profiles the structure of more than 1,750 RNAs at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(149 citation statements)
references
References 49 publications
10
136
0
Order By: Relevance
“…This expression profile suggests that Y. pseudotuberculosis is not exposed to reactive oxygen species produced by neutrophils and other innate immune cells. However, a recent study showed that the production of multiple Yersinia catalases, superoxide dismutases, and thioredoxin (katA, sodB, sodC, and trxA) is controlled on the posttranscriptional level by thermoresponsive RNA structures (RNA thermometers) (70). They act as translational repressor elements at lower temperature but not at 37°C, and they are thus not detectable by conventional RNA-seq.…”
Section: Resultsmentioning
confidence: 99%
“…This expression profile suggests that Y. pseudotuberculosis is not exposed to reactive oxygen species produced by neutrophils and other innate immune cells. However, a recent study showed that the production of multiple Yersinia catalases, superoxide dismutases, and thioredoxin (katA, sodB, sodC, and trxA) is controlled on the posttranscriptional level by thermoresponsive RNA structures (RNA thermometers) (70). They act as translational repressor elements at lower temperature but not at 37°C, and they are thus not detectable by conventional RNA-seq.…”
Section: Resultsmentioning
confidence: 99%
“…A fruitful approach might be to use new advantages in RNA sequencing to define the secondary structure of all transcripts in a bacteria (the ‘structurome’) at one temperature and compare it with another temperature. The Narberhaus laboratory has successfully used such an approach on RNA isolated from Yersinia pseudotuberculosis to identify and characterise more than a dozen new thermosensors (Righetti et al, ). Using a similar methodology but in vivo, we have recently identified a new ‘cold sensing’ thermosensor in Listeria monocytogenes controlling expression of a cold shock protein (Ignatov and Johansson, unpublished results).…”
Section: Future Visions—the Global Warming Of Rna Thermometers?mentioning
confidence: 99%
“…Surprisingly, so far only one RNAT has been identified and characterized in Y. pseudotuberculosis, the lcrF RNAT located in the intergenic region of the yscWlcrF operon [42] [44]. In addition to translation, the transcription of many RNAT-controlled genes (e.g.…”
Section: Rna Thermometers (Rnats)mentioning
confidence: 99%
“…In addition to translation, the transcription of many RNAT-controlled genes (e.g. lcrF, ailA, cnfY, katA, sodA, sodB and sodC) is also activated upon thermal upshift from moderate to host body temperature [16,44]. This highlights the importance of a fine-tuned and multilayered control to rapidly adjust the pathogens' demands upon host entry.…”
Section: Rna Thermometers (Rnats)mentioning
confidence: 99%